Warmer and drier conditions have increased the potential for large and severe fire seasons across south‐eastern Australia. Issue 10 (26th April 2022) - Collins, Luke; Clarke, Hamish; Clarke, Michael F.; McColl Gausden, Sarah C.; Nolan, Rachael H.; Penman, Trent; Bradstock, Ross
Abstract: Aim: The aims were: (1) to identify the environmental drivers of interannual variation in wildfire extent and severity; (2) to examine temporal trends in climatic potential for large and severe wildfires; and (3) to assess whether environmental conditions experienced during the 2019–2020 mega‐fire season were anomalous. Location: South‐eastern Australia. Time period: 1953–2020. Major taxa studied: Temperate forests. Methods: We used satellite‐derived fire severity mapping from 1988 to 2020 to model the effects of drought, weather and fuels on the annual area burned and the proportion of the area burned that was impacted by high‐severity fire across four bioregions. Trends in wildfire extent and severity were then estimated from 1953 to 2020 using these derived models and gridded climate data to assess changes in climatic potential for large and severe wildfires. Estimates of wildfire extent and severity for the 2019–2020 fire season were then assessed against prior seasons (1953–2019). Results: Annual area burned was positively related to the severity of seasonal drought and frequency of fire weather conditions that promote substantial daily fire growth. Wildfire severity was elevated in years with severe fire weather and increased with increasing antecedent drought in years without severe fire weather. Fuels had a lesser effect on wildfire extent and severity than climate. Potential fire extent and severity have increased over time in response to an increased severity of drought and worsening fire weather conditions. Estimates of wildfire extent and severity during the 2019–2020 fire season approached the upper extreme within each bioregion, owing to widespread extreme climatic conditions. Main conclusions: The climatic potential for large and severe forest fires has increased across south‐eastern Australia since the 1950s, probably because of anthropogenic climate change. The magnitude and severity of the 2019–2020 fires reflected climatic conditions that are driving an increase in the size and severity of wildfires.